Implementation of "Jakarta Smart City" In One-Stop-Service: Daily Need In The City South Jakarta? - Afika Sari Dewi; Bhakti Nur Avianto (Journal Research of Social Science, Economics, and Management, 2023)
This paper aims to discuss the implementation of the “Jakarta Smart City” (JAKI) application policy in the South Jakarta City area in 2020. And to find out more about the implementation and the supporting and inhibiting factors for the JAKI application. This research focuses on the implementation of the "JakLapor" feature found in the JAKI application. This study uses four indicators obtained from George C. Edward III's policy implementation theory, namely Communication, Resources, Disposition and Bureaucratic Structure. This study uses a qualitative approach, using primary and secondary data sources—obtained Primary data sources from observations and interviews with informants—received Secondary data sources from document searches. The study results indicate that the JAKI application in South Jakarta City has not utilized technology and communication to realize better public services. The use of Smart City has also not succeeded in increasing public and government participation in using application data, providing input and criticism of the implementation of public services. Furthermore, the JAKI application also has supporting and inhibiting factors in its application. However, there are also challenges in implementing Smart City in Indonesia, such as inadequate infrastructure, data security problems, and limited access to technology for people in rural areas. Therefore, there is a need for collaboration between the government, private sector, and society to overcome these challenges and ensure the implementation of a sustainable and inclusive Smart City in Indonesia.